Oxidative stress and retinopathy of prematurity [Oksidatif stres ve prematüre retinopatisi] - ÇEKİÇ, OSMAN (Turkish Ophthalmology Society, 2014)
Oxidative stress plays an important role in the etiology of retinopathy of prematurity. Insuffcient antioxidant system and increased oxidative stress in premature infants lead to the development of the disease. Understanding the mechanism of oxidative stress and antioxidant system and the related signaling pathways contribute to the development of novel options for diagnosis and treatment of retinopathy of prematurity. The current review aimed to evaluate the relationship between oxidative stress and retinopathy of prematurity and to create a current notion regarding this issue.
Keywords: Antioxidant; Oxidative stress; Reactive oxygen species; Retinopathy of prematurity